Studi Perbandingan Perilaku Struktur Gedung Bertingkat Tahan Gempa Menggunakan Material Beton Bertulang Dan Baja - Muhammad Andi Arif; Pio Ranap Tua Naibaho (Jurnal Konstruksi, 2025)
The construction of high-rise buildings is influenced by land limitations and advances in construction technology. However, these structures present more complex technical risks, particularly in earthquake-prone regions such as Indonesia. Earthquake-resistant structural design serves as a preventive approach to minimize potential casualties and post-disaster losses, rather than to create completely earthquake-proof buildings. Concrete and steel are commonly used structural materials in high-rise buildings due to their high strength, but their selection also considers various other parameters beyond strength alone. This study analyzes the comparative seismic performance of high-rise building models using steel and reinforced concrete materials. The analysis focuses on base shear force, inter-story drift response, and the impact of P-Delta effects using the response spectrum method in ETABS v.21 software. The results show that the total base shear force (Vtotal) in the Reinforced Concrete Structure (RCS) model is 28,979.31 kN, while in the Steel Structure (SS) model it is 8,133.61 kN. The higher value in the RCS model is due to its greater structural weight and shorter structural period. Both models meet the allowable inter-story drift limits, with the RCS model showing smaller displacements: 50.001 mm (X direction, 10th floor) and 41.058 mm (Y direction, 9th floor), compared to the SS model’s 50.930 mm (X direction, 8th floor) and 40.700 mm (Y direction, 7th floor). Furthermore, the P-Delta effect in both models remains within safe limits; however, the RCS model exhibits smaller maximum values of 0.0220 and 0.0185 compared to the SS model’s 0.0649 and 0.0530, indicating better seismic stability in the reinforced concrete structure.